2018
DOI: 10.1121/1.5030925
|View full text |Cite
|
Sign up to set email alerts
|

A transverse isotropic equivalent fluid model combining both limp and rigid frame behaviors for fibrous materials

Abstract: Due to the manufacturing process, some fibrous materials like glasswool may be transversely isotropic (TI): fibers are mostly parallel to a plane of isotropy within which material properties are identical in all directions whereas properties are different along the transverse direction. The behavior of TI fibrous material is well described by the TI Biot's model, but it requires one to measure several mechanical parameters and to solve the TI Biot's equations. This paper presents an equivalent fluid model that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 50 publications
(77 reference statements)
1
15
0
Order By: Relevance
“…In the case of glass wool, the model can consider a specific scenario of anisotropy such as transversely isotropic (TI) properties. As Nennig indicates [6,15], the equivalent bulk modulus in the JCA model of a TI fluid, will not be affected by anisotropy, therefore yields…”
Section: The Jca Model With Orthotropic Airflow Resistivitymentioning
confidence: 98%
See 3 more Smart Citations
“…In the case of glass wool, the model can consider a specific scenario of anisotropy such as transversely isotropic (TI) properties. As Nennig indicates [6,15], the equivalent bulk modulus in the JCA model of a TI fluid, will not be affected by anisotropy, therefore yields…”
Section: The Jca Model With Orthotropic Airflow Resistivitymentioning
confidence: 98%
“…A semi phenomenological equivalent fluid model, the Johnson-Champoux-Allard (JCA) [5,6,11,15] model, and a diphasic model, the Biot-Allard [4,6] model (denoted Biot hereafter) are used for describing the wave propagation. The JCA model yields an equivalent density ρ eq and equivalent bulk modulus K. The Biot model yields the characteristic impedance Z c and the complex wavenumber k. These four properties (ρ eq , K, Z c , k) can be used to calculate the sound absorption coefficients α.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work 6 have shown that anisotropic materials can have different apparent sound speed depending on the direction of propagation, coupling viscous and inertial regimes. This is especially visible at grazing angles of incidence, and can be exploited for absorption considering a diffuse field where all incidences are accounted for.…”
Section: Introductionmentioning
confidence: 99%